PENYULUHAN KURATIF BEKERJASAMA DENGAN PUSKESMAS DESA SANGEH DALAM PEMERIKSAAN DAN EDUKASI PENATALAKSANAAN HIPERTENSI KEPADA MASYARAKAT DI POSYANDU BANJAR TEGAL GERANA DESA SANGEH - Luh Adi Kusuma; Putu Dian Marani Kurnianta; Gusti Ayu Dewi Lestari; Ni Komang Ayu Dyah Pramesti; Ni Ketut Sindia Wati; Ni Putu Nita Lusiana Dewi; Ni Kadek Saskya Pratiwi; Faisal Oktaviani Pratama Abiansyah; Patricia Novica Dua Poa (JPMUJ, 2025)
Hypertension is one of the most prevalent non-communicable diseases and a major contributor to morbidity and mortality rates in Indonesia. In Banjar Tegal Gerana, Sangeh Village, hypertension cases remain high, while public awareness regarding its management is relatively low. Therefore, a community service program was carried out in the form of curative health education aimed at increasing public knowledge about hypertension. This activity was conducted collaboratively between pharmacy students and healthcare professionals from the local public health center (Puskesmas). A total of 35 participants attended the session, which covered topics including the definition, risk factors, symptoms, complications, types of antihypertensive drugs, and how to measure blood pressure independently. A structured questionnaire was used as an instrument to assess knowledge through pretest and posttest evaluations. Data analysis using the Shapiro-Wilk test confirmed that the data were normally distributed (p > 0.05), allowing for further analysis using a Paired T-Test, which revealed a significant difference between pretest and posttest scores (p < 0.001). These findings indicate that the educational intervention effectively improved participants' knowledge. This program demonstrates that collaborative education between students and health professionals can serve as an effective promotive and preventive strategy for enhancing public awareness and independent management of hypertension.